The Untold Story of Internal Migration in Germany: Life-Cycle Patterns, Developments, and the Role of Education - Anton Barabasch; Kamila Cygan-Rehm; Guido Heineck; Sebastian Vogler (Institute of Labor Economics (IZA), 2025)
This paper examines internal migration from a lifetime perspective using unique data on detailed residential biographies of individuals born in Germany between 1944 and 1986. We first describe life-cycle patterns of internal mobility and potential differences across space, time, and socio-demographic groups. We find substantial differences across the life course, with major location changes around important educational decisions and striking differences across groups, especially by educational attainment. We then investigate causality in the substantial education-mobility gradient. For identification, we exploit two policy-induced sources of variation, each shifting towards better education at a different margin of the ability distribution. Using a difference-in-differences and a regression discontinuity design, we find no effect of these policies on internal mobility.
Keywords: I26; J61; R23; 330; compulsory schooling; education; Germany; internal migration; regional mobility; enrollment cutoffs